Hexahelix Collaboration to Boost SME Investment - Muchtar, Aiman Aditya; Dinanty, Yolanda Dara; Khumayah, Siti; Rahmayanti, Rahmayanti (Indonesian Journal of Advanced Research, 2025)
This study examines the Hexahelix collaboration in increasing investment in MSMEs through the SME Mall Program in Cirebon City, using Ansell and Gash’s collaborative governance theory. A qualitative descriptive method was employed, with data collected through interviews, observations, documentation, and literature review. The analysis focused on four indicators: initial conditions, institutional design, facilitative leadership, and collaborative process. Findings reveal that the Hexahelix model has moderately succeeded in boosting investment but faces challenges such as communication gaps, product layout limitations, and lack of coordination with government agencies. Despite these, the program demonstrates potential in supporting MSMEs. The study recommends strengthening institutional collaboration, implementing clearer policies, and conducting regular evaluations to enhance program effectiveness.